2020
DOI: 10.1103/physrevphyseducres.16.023101
|View full text |Cite
|
Sign up to set email alerts
|

Active learning reduces academic risk of students with nonformal reasoning skills: Evidence from an introductory physics massive course in a Chilean public university

Abstract: We present the findings of a pilot plan of active learning implemented in introductory physics in a Chilean public university. The model is research based as it considered a literature review for adequate selection and design of activities consistent with the levels of students' reasoning skills. The level of scientific reasoning is positively correlated to student success. By contrast to a control group of students following traditional lectures, we observed a significant reduction in failure rate for student… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Additionally, without knowing when and how students and teachers will return to the classroom, we developed this proposal as an alternative for teachers and researchers who seek to improve students' well-being as they take their courses. distractions, set clear learning goals, and provide opportunities for interaction in safe spaces for students to ask questions (Lagubeau et al, 2019). Although designed to improve learning, teaching methodologies alone, such as problem-based learning, collaborative learning, and project-based learning (Davis & McPartland, 2012), do not end apathy, lack of commitment, and the inattention of students (Gomez-Chacón, 2000;Rincon-Flores, Lopez-Camacho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, without knowing when and how students and teachers will return to the classroom, we developed this proposal as an alternative for teachers and researchers who seek to improve students' well-being as they take their courses. distractions, set clear learning goals, and provide opportunities for interaction in safe spaces for students to ask questions (Lagubeau et al, 2019). Although designed to improve learning, teaching methodologies alone, such as problem-based learning, collaborative learning, and project-based learning (Davis & McPartland, 2012), do not end apathy, lack of commitment, and the inattention of students (Gomez-Chacón, 2000;Rincon-Flores, Lopez-Camacho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Morze et al (2021) declare that Adaptive Learning technologies aim to provide students with the means to acquire information according to their training needs and cognitive differences. Lagubeau et al (2020) state that these technologies also promote active learning, and González Fernández et al (2018) indicate that they also promote self-regulation. Students take control of their learning process; they can access learning resources according to their needs and study them at their own pace.…”
Section: Adaptive Learningmentioning
confidence: 99%
“…Bergmann and Sams (2012) indicate that "flipping" the classroom establishes a structure to ensure students receive a personalized education tailored to their needs. Lagubeau et al (2020) indicate that Flipped Learning aims to optimize class time by promoting active learning. Van Alten et al (2019) say that some studies have found that using Flipped Classroom strategies improves learning compared to traditional teaching methods.…”
Section: Adaptive Learningmentioning
confidence: 99%
“…According to several studies, students who utilize scientific reasoning may have the following advantages: (1) long-term academic performance, (2) cognitive abilities, (3) decision-making abilities, and (4) problem-solving abilities in daily life (Abate et al, 2021;Mitash et al, 2022;Speirs et al, 2021). Some researchers argue that people who can think critically and creatively, and evaluate and criticize information with reliable evidence are the ones who can survive in the face of uncertain progress and global challenges (Ding, 2018;Lagubeau et al, 2020). This causes the nation, educators, and researchers to pay much attention to the development of scientific knowledge and scientific reasoning abilities.…”
Section: Introductionmentioning
confidence: 99%